(untitled) (Altre Modernità, 2011)
Fifty years after, Frantz Fanon’s The Wretched of the Earth continues to be one of theoretical models of black radical tradition. The thought of Frantz Fanon was also problematized by the constellation of writers who were engaged in the construction of postcolonial literary identity. The story of the relationship between Fanon and the national liberation movements in Angola illuminates not only political and military processes of decolonization in Africa but also the influence of Fanon’s thought. In the Pepetela’s novel, A Geração da Utopia (1992), Elias as a fanonian misreader, reformulates the Fanon’s thought to defend a racial position of UPA (União das Populações de Angola).